Vitamin D in Injury Risk and Healing- A Comprehensive Review - Jętasiewicz, Igor; Górski, Szymon; Okupniarek, Joanna; Bartosik, Michalina; Oborski, Michał; Oborski, Krzysztof; Miarczyński, Jakub; Barczyńska, Katarzyna (Journal of Education, Health and Sport, 2026)
In an era of an aging population, vitamin D deficiencies constitute a significant clinical problem. Its pleiotropic effects encompass key reparative processes in soft and bone tissues, as well as modulation of the nervous and immune systems, suggesting its potentially important role in injury prevention and healing support. The aim of this review was to systematically analyse and synthesise current knowledge regarding: (1) the molecular mechanisms of vitamin D action in repair processes, (2) the efficacy of its supplementation in the context of post-injury healing, and (3) the clinical consequences of its deficiency. The literature review was conducted according to the PRISMA methodology. The PubMed, Scopus, and Web of Science databases were searched using defined keywords related to vitamin D, wound healing, bone regeneration, and trauma. Original and review articles published between 2010 and 2024 were analysed. The synthesis confirmed the key role of vitamin D in regulating cell proliferation, angiogenesis, extracellular matrix synthesis, and inflammation modulation. Clinical data indicate that supplementation is most beneficial for patients with pre-existing deficiency, significantly reducing the risk of complications and improving healing parameters. Groups at particular risk of deficiency requiring monitoring include the elderly, burn victims, diabetics, individuals with dark skin phototypes, and those with malabsorption disorders. For patients with normal or high baseline 25(OH)D levels, the benefits of supplementation are limited or insignificant. Optimising vitamin D levels is a significant, modifiable factor supporting tissue healing, especially in deficient patients. Routine assessment of vitamin D status and targeted supplementation in risk groups should be an integral part of comprehensive post-traumatic care.